2017
DOI: 10.1104/pp.16.00581
|View full text |Cite
|
Sign up to set email alerts
|

Dead or Alive? Using Membrane Failure and Chlorophyll a Fluorescence to Predict Plant Mortality from Drought

Abstract: Climate models predict widespread increases in both drought intensity and duration in the next decades. Although water deficiency is a significant determinant of plant survival, limited understanding of plant responses to extreme drought impedes forecasts of both forest and crop productivity under increasing aridity. Drought induces a suite of physiological responses; however, we lack an accurate mechanistic description of plant response to lethal drought that would improve predictive understanding of mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 92 publications
(162 reference statements)
2
96
0
Order By: Relevance
“…Moreover, upon exposure to both stresses at the same time, the lentil leaves showed extensive damage to their membranes (as indicated by high EL), chlorophyll content, and photosynthetic efficiency, which might be attributed to a significant reduction in leaf water status and stomatal conductance (Awasthi et al, 2014). Damage to membranes may occur due to the direct impacts of these stresses (Guadagno et al, 2017;Horváth et al, 2012) or intense oxidative stress generated by two stresses (Johnson et al, 2014) and has been reported in chickpea (Awasthi et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, upon exposure to both stresses at the same time, the lentil leaves showed extensive damage to their membranes (as indicated by high EL), chlorophyll content, and photosynthetic efficiency, which might be attributed to a significant reduction in leaf water status and stomatal conductance (Awasthi et al, 2014). Damage to membranes may occur due to the direct impacts of these stresses (Guadagno et al, 2017;Horváth et al, 2012) or intense oxidative stress generated by two stresses (Johnson et al, 2014) and has been reported in chickpea (Awasthi et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, upon exposure to both stresses at the same time, the lentil leaves showed extensive damage to their membranes (as indicated by high EL), chlorophyll content, and photosynthetic efficiency, which might be attributed to a significant reduction in leaf water status and stomatal conductance (Awasthi et al, ). Damage to membranes may occur due to the direct impacts of these stresses (Guadagno et al, ; Horváth et al, ) or intense oxidative stress generated by two stresses (Johnson et al, ) and has been reported in chickpea (Awasthi et al, ). Chlorophyll loss is attributed to increased photo‐oxidation (Guo, Zhou, & Zhang, ), dehydration, inhibited synthesis, or increased degradation (Tewari & Tripathy, ), which matches the observations in chickpea (Awasthi et al, ), tomato (Nankishore & Farrell, ), and rice (Kumar, Vijayalakshmi, & Vijayalakshmi, ) exposed to both stresses.…”
Section: Discussionmentioning
confidence: 99%
“…and finally, Ψ min calculated as Ψ min = E max /K plant . The maximum quantum efficiency of photosystem II ( F v / F m ) is a well-known parameter typically used as an index of photosynthetic potential and injury in leaves (Guadagno et al, 2017). Here, we assessed F v / F m in the same plants used for the OV method over the desiccation course as a proxy for leaf damage.…”
Section: Maximum Leaf Hydraulic Conductancementioning
confidence: 99%
“…Consequently, the growth cannot resume since there is no more meristematic cells or any parenchyma cells that can dedifferentiate. On the contrary, when PLD max was not reached, the growth resumed despite a dead volume in the branches, involving an active cambium that generates new xylem vessels to recover from an episode of drought (Brodribb et al, 2010; Guadagno et al, 2017)…”
Section: Discussionmentioning
confidence: 99%
“…According to Li et al, (2015) and Guadagno et al, (2017), a threshold in the cell death (membrane injury or mortality of cambial cells) can be a point of no return associated with plant death. Maintaining the stability of cell membranes is an integral part of drought tolerance (Bajji et al, 2002).…”
Section: Discussionmentioning
confidence: 99%